2020
DOI: 10.3390/app10010417
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Characteristics and Antifungal Activity of Lactobacillus plantarum and Its Impact on Fermentation of Italian Ryegrass at Low Moisture

Abstract: The study aimed to investigate probiotic characteristics, and low moisture silage fermentation capability of selected lactic acid bacteria (LAB) isolated from Alfalfa (Medicago sativa L). Morphological and physiological properties, carbohydrates fermentation, enzymes, and organic acids production, anti-fungal activity, antibiotic sensitivity patterns, and probiotic characteristics (acidic and bile salt tolerances, hydrophobicity and aggregations natures) of LAB were examined. 16SrRNA sequencing was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Some characteristics have been considered for probiotic selection that includes surviving in the foodstuff at a high cell density and viable in stable throughout the shelf life of a product, acid, bile salt, simulated gastric or intestinal transit, adhere and colonize epithelial cells, inhibition of pathogens and prebiotic-utilizing capability. 28,33,42,60 In this aspect, we analyzed the above criteria for A29 in an in vitro model. The results indicated that A29 survived in significant numbers in simulated gastric, duodenal, and intestinal juices in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some characteristics have been considered for probiotic selection that includes surviving in the foodstuff at a high cell density and viable in stable throughout the shelf life of a product, acid, bile salt, simulated gastric or intestinal transit, adhere and colonize epithelial cells, inhibition of pathogens and prebiotic-utilizing capability. 28,33,42,60 In this aspect, we analyzed the above criteria for A29 in an in vitro model. The results indicated that A29 survived in significant numbers in simulated gastric, duodenal, and intestinal juices in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent reports claimed that the use of the probiotics and or prebiotics could efficiently reduce serum/ plasma cholesterol level and improved overall lipid profiles. 27 Especially, lactobacillus could be considered as potential probiotic strains [28][29][30] and exhibits strong hypocholesterolemic effects in in vivo. 20,26 Lactobacillus not only influences its effect on cholesterol and triglyceride metabolism, but also sustains the gut-associated microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested that inoculation may influence the digestibility of DM because of a probiotic effect on the rumen microbial population. This possible probiotic effect has become the focus of studies and the screening of strains as potential inoculants for silages (Ellis et al 2016;Rabelo et al 2017;Srigopalram et al 2017;Soundharrajan et al 2019;Muthusamy et al 2020). Strains that improve quality and reduce losses in silage as well as have a possible probiotic effect on animals have been reported by Ellis et al (2016), Soundharrajan et al (2019) and Muthusamy et al (2020).…”
Section: Evaluation Of Animal Performance According To the Addition Omentioning
confidence: 99%
“…This possible probiotic effect has become the focus of studies and the screening of strains as potential inoculants for silages (Ellis et al 2016;Rabelo et al 2017;Srigopalram et al 2017;Soundharrajan et al 2019;Muthusamy et al 2020). Strains that improve quality and reduce losses in silage as well as have a possible probiotic effect on animals have been reported by Ellis et al (2016), Soundharrajan et al (2019) and Muthusamy et al (2020). Strains are tested for properties such as autoaggregation, coaggregation, hydrophobicity and bile resistance (Srigopalram et al 2017;Soundharrajan et al 2019;Muthusamy et al 2020).…”
Section: Evaluation Of Animal Performance According To the Addition Omentioning
confidence: 99%
See 1 more Smart Citation